Cross-country comparisons of efficiency: Evidence from the UK and Italian investment firms - Beccalli, Elena (Journal of Banking & Finance, 2004)
This paper compares and reconciles two new methods for cross-country comparisons of the cost efficiency of UK and Italian investment firms over the period 1995–1998. It employs four different specifications of the stochastic frontier methodology, using a translog cost function in order to measure X-efficiency. The traditional common frontier reveals that Italian investment firms are nearly as efficient as UK firms. To overcome traditional limitations, two methods are used in this paper. They provide consistent results. The first method shows differences between the efficiency of the two countries by incorporating environmental variables into the cross-country common frontier. The second method shows differences in the efficiency of the domestic versus foreign investment firms in the two countries, by testing the ability to monitor and control on a cross-border basis. Finally, to identify investment firms that are both cost and profit efficient, we undertake a profitability test.